Potential role of the interaction between equine estrogens, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) in the prevention of coronary heart and neurodegenerative diseases in postmenopausal women - Perrella, Joel (BioMed Central, 2003)
BACKGROUND: An inverse relationship between the level of high-density lipoprotein (HDL) and coronary heart disease (CHD) has been reported. In contrast, oxidized HDL (oHDL) has been shown to induce neuronal death and may play an important role in the pathogenesis of CHD. In the present study we have investigated a: the effect of various equine estrogens on HDL oxidation, b: the inhibition of LDL oxidation by HDL and c: the effect of these estrogens on LDL oxidation in the presence of HDL. RESULTS: All 11 equine estrogens tested protected the HDL from oxidation in a concentration dependant manner. Equilenin, 17β-dihydroequilenin, and 17α-dihydroequilenin (Δ(6–8)-estrogens) were found to be the most potent inhibitors of HDL oxidation. Some of the novel ring B unsaturated estrogens were 2.5 to 4 times more potent inhibitors of HDL oxidation than 17β-estradiol. HDL was found to delay LDL oxidation. The protection of LDL oxidation by HDL is enhanced by the addition of estrogen, with equilenin being again more potent than 17β-estradiol. CONCLUSIONS: Equine estrogens can differentially inhibit the oxidation of HDL with the Δ(6–8)-estrogens being the most potent antioxidants. The ability of estrogens to enhance HDL's antioxidant activity is to our knowledge the first report of an interaction of estrogen with HDL that results in the delay or inhibition of LDL oxidation. This may be another mechanism by which estrogens may reduce the risk of CHD and neurodegenerative diseases in healthy and younger postmenopausal women.